(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
4-Hydroxy-3-(2-chlorprop-2-enyl)-2-methylquinolines were synthesized by O-allylation of corresponding 4-hydroxy-2-methylquinolines and further rearrangement of resulting 4-(2-chlorprop-2-enyloxy)-2-methylquinolines. As a result of following reactions, they were converted to 4-amino-3-(2’-methylindolyl-3’)-2-methylquinolines.